Counseling of Infectious Diseases Related to Stunting and Its Prevention in Koroncong Village, Keroncong District, Pandeglang Regency, Banten Province - Dian Mardhiyah; Dini Widiyanti; Siti Maulidya Sari; Kholis Ernawati; R.W Susilowati (Majalah Sainstekes, 2021)
Infectious disease is one of the direct causes of nutritional status problems in children age 0-59 months. Stunting is a chronic malnutrition problem that has received attention recently. The Koroncong village area had a total of 63 children age 0-24 months, with the incidence of stunting as many as 19 children (32%) in September 2019. Koroncong village was one of 10 locus stunting villages in Pandeglang. The purpose of this study was to increase the knowledge of mothers with children age 0-24 months about infectious diseases that contribute to disrupt child development and prevention, training cadres on how to anthropometric measurement children age 0-24 months to detect stunting. The method used One Groups Pretest-Posttest Design with counseling for mothers with children age 0-24 months and training of cadres and using total sampling for 63 mothers with children aged 0-24 months and 14 cadres. The results of research before and after counseling showed an increase in the knowledge of 50 respondents who attended, seen from the pretest and posttest mean value of 24.50 and also found p-value 0.000 with the Wilcoxon test. There was an increase in the cadres' ability to use early detection stunting mats (p-value 0,000) with the paired T test. The activities carried out are expected to increase knowledge and change the attitudes of mothers with children aged 0-24 months against infectious diseases related to stunting and their prevention, as well as improve cadres' skills in detecting stunting in children so that a healthy generation is created.